Dietary nitrate supplementation improves rowing performance in well-trained rowers - Bond, H.; Morton, L.; Braakhuis, A. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2012)
Increased plasma nitrate concentrations from dietary sources of nitrate have proven to benefit exercise performance. Beetroot (BR) contains relatively high levels of nitrate (NO3-), which increases nitric oxide stores. This study investigated whether dietary nitrate supplementation, in the form of a BR beverage, would improve rowing performance during ergometer repetitions. In a randomized crossover design, 14 well-trained junior male rowers consumed 500 ml of either BR or placebo (PL) daily for 6 d. After supplementation, rowers completed 6 maximal 500-m ergometer repetitions and times were recorded. A 7-d washout period separated the 2 trials. Blood pressure, oxygen saturation, maximum heart rate, urine (specific gravity, pH, and nitrites), and lactates were collected for analysis at baseline and pre- and postperformance. Changes in the mean with 95% confidence limits were calculated. There was a likely benefit to average repetition time in the BR condition, compared with PL (0.4%, 95% confidence limits, ± 1.0%). In particular, Repetitions 4-6 showed an almost certain benefit in rowing time on BR (1.7%, 95% CL, ± 1.0%). The underlying mechanism for the observed results remains unknown, as differences observed in rowers` physiological measures between the 2 conditions were unclear. Conclusively, nitrate supplementation in the form of BR juice resulted in improved maximal rowing-ergometer repetitions, particularly in the later stages of exercise.